PENGARUH EKSTRAK AIR BAWANG PUTIH (Allium sativum) TERHADAP MORTALITAS LARVA Crocidolomia binotalis PADA TANAMAN KUBIS - Debby Moniharapon; Maria Nindatu (BIOPENDIX, 2015)
Background: Garcil (Allium sativum) is an important commodity and has high economic value in Indonesia.Studies have been using water extracts of garcil as larval mortality Crocidolomia binotalis in august –september 2014. This study aimed to determine the effect of water extract of Garlic (Allium sativum) on mortality of larvae on cabbage plants Crocidolomia binotalis. Methods: This study was an experimental study, using a rando mized block design (RBD), using the control group, and treatment concentraction of water extracts of garlic (Allium sativum). Concentration ranging from 2%, 4%, 6%, 8% with observation for 24 hours. Data effect of aqueous extract of garlic is effective against larval mortality Crocidolomia binotalis analyzed by real difference test (LSD) and the determination of the value of LC50, using SPSS. Result: The results showed the water extract of garlic is effective for larval mortality Crocidolomia binotalis is the concentration of 6% and of probit analysis LC50 values of 4,632%. Conclusion: Concentration of 4,632% aqueous extract of garlic (Allium sativum) can kill larvae Crocidolomia binotalis after administration of the extract and observation for 24 hours